1980
DOI: 10.3382/ps.0590647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Environment and Pinealectomy on Growth and Thyroid Function in the Broiler Cockerel

Abstract: Four replicate experiments were conducted to determine the effects of pinealectomy and environmental lighting on growth and thyroid function in broiler cockerels. Birds were housed in battery brooders under a 14L:10D white light regime for 2 weeks and then allotted to lightcontrolled chambers. The light environments were 14L:10D white, 14L:10D green (narrow band, 545 nm peak), and constant dark. Surgery was performed when the chicks were 3 to 5 days old. At the end of the 32-day experimental period, weight gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…This observation does not support a previous study on cockerels (Osol et al 1980) in which pinealectomy was found not to affect levels of plasma thyroid hormones. However, the depressive action of the pineal gland on levels of plasma T4 is consistent with an inhibi¬ tory action of the pineal gland on the neuroendocrinethyroid axis as has been demonstrated in the rat and hamster (Vaughan et al 1982;Vriend, 1983).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This observation does not support a previous study on cockerels (Osol et al 1980) in which pinealectomy was found not to affect levels of plasma thyroid hormones. However, the depressive action of the pineal gland on levels of plasma T4 is consistent with an inhibi¬ tory action of the pineal gland on the neuroendocrinethyroid axis as has been demonstrated in the rat and hamster (Vaughan et al 1982;Vriend, 1983).…”
Section: Discussioncontrasting
confidence: 99%
“…In birds, the role of the pineal gland in the control of thyroid function is uncertain. Pinealectomy in the quail causes an increase in the weight of the thyroid glands (Oishi & Lauber, 1974) but it was found not to affect levels of plasma thyroid hormones in cockerels exposed to 14h light: 10h darkness (14L: 10D) or to constant darkness (Osol, Ross & Carew, 1980) or to different ambient temperatures (Cogburn & Harrison, 1980). The present study was carried out in the chicken to determine whether the pineal gland plays a role in regulating levels of plasma T4 and T3, taking into account the daily rhythms in plasma levels of these hormones (Klandorf, Sharp & Duncan, 1978a;Klandorf, Sharp & MacCleod, 1981a;Klandorf, Sharp & Newcomer, 198le;Sharp & Klandorf, 1984).…”
mentioning
confidence: 97%
“…These observations suggest improved performance could be obtained by tailoring the light wavelength environment as the bird ages. These observations may be related to the age-pineal-thyroid functions suggested by Oishi and Lauber (1974) and Osol et al (1980).…”
Section: (G)mentioning
confidence: 75%
“…Evaluation of the effect of energy-efficient light sources on laying hens suggests wavelengths being emitted may (Siopes and Wilson, 1980;Pyrzak et al, 1984Pyrzak et al, , 1986 or may not (Fitzsimmons and Cha, 1985;Darre and Spandorf, 1985) affect productivity. Foss et al (1972), Wabeck and Skuglund (1974), and Osol et al (1980) have shown that broiler performance is affected by the wavelength of light. Generally, these studies using monochromatic light suggest blue or green wavelengths enhance growth rate whereas red inhibits growth.…”
Section: Introductionmentioning
confidence: 99%
“…Ballard and Biellier (1975) reported that pinealectomy (PX) did not affect feed intake rhythms in adult chickens. Studies with immature chickens have demonstrated that the pineal gland can influence growth rates and feed efficiency, and this apparently does not involve any persistent change in feed intake, thyroid function, or metabolism (Cogburn and Harrison, 1977;Darre et al, 1980;Osol et al, 1980). Sayler and Wolfson (1968a,b) reported that PX of immature quail did not influence body weight but that blinding of intact or pinealectomized quail depressed body weight in females but not males.…”
Section: Introductionmentioning
confidence: 99%